Characterization of the lncRNA-miRNA-mRNA regulatory network to reveal potential functional competing endogenous RNAs in traumatic brain injury - Yu, Jiangtao; Lu, Zijun; Liu, Ruining; Wang, Pengcheng; Ma, Haoli; Zhao, Yan (Frontiers in Neuroscience, 2023)
Traumatic brain injury (TBI) is one of the most common acute central nervous system injury diseases. Given the medical and socio-economic burdens of TBI patients, the pathogenesis in TBI and the latent intervention targets needed to be further illuminated. Long non-coding RNAs (lncRNAs) had been revealed to play a vital role in the regulation of pathogenesis after TBI. However, the mutual communication and adjustment of lncRNA associated competing for endogenous RNA (ceRNA) networks in TBI have not been explored to date. In this study, we systematically sequenced the whole transcriptome of lncRNAs, miRNAs, and mRNAs between sham and TBI groups and a total of 939 differentially expressed (DE) lncRNAs, 46 DE miRNAs, and 1,951 DE mRNAs were obtained. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and protein interaction relationship analyses were conducted for DE mRNAs to identify hub DE genes in TBI. Based on the criteria of bioinformatics prediction, the lncRNA associated ceRNA network covering 201 lncRNAs, 22 miRNAs, and 79 mRNAs was constructed. This study provides a novel perspective on the molecular mechanism of lncRNA in TBI and identifies certain lncRNAs as potential therapeutic targets against TBI.